Systematic characterization of biocrude and aqueous phase from hydrothermal carbonization of algal biomass. Issue 3 (June 2022) - Jabeen, Sidra; Gao, Xiangpeng; Hayashi, Jun-ichiro; Altarawneh, Mohammednoor; Dlugogorski, Bogdan Z.
Abstract: This contribution evaluates the impacts of reaction conditions on the yields and properties of biocrude and aqueous phase from hydrothermal carbonization (HTC) of Chlorella vulgaris (solid loading: 10.0 wt%) at 180 – 220 °C for 15 and 60 min. The results indicate that increasing HTC temperature ( T HTC ) from 180 to 220 °C enhances biocrude yield from 8.8 to 34.6 wt%, for the holding time ( t h ) of 60 min, and from 4.9 to 26.0 wt% for 15 min. The carbon recovery and higher heating value (HHV) of biocrude elevate with increasing both T HTC and t h, with the highest values of 50.6% and 34.0 MJ/kg, respectively, observed at 220 °C and 60 min. Among inorganic species, Na, Fe, and Zn display reasonable retentions in the biocrude with a pronounced effect of T HTC observed at 15 min. The yield of aqueous phase increases first when T HTC rises from 180 to 200 °C but decreases with further increasing T HTC to 220 °C due to the re-polymerization of water-soluble organics into biocrude and/or the formation of gaseous products. The aqueous phase experiences a reduction of total organic carbon with increasing reaction severity because of the transfer of carbon to biocrude and/or gases. The aqueous phase is rich in organic nitrogen, dihydrogen phosphate, acetate, and potassium, which are required for its recycling as cultivation media. The concentrations of heavy metals (Fe, Cr, Mn, Co, Ni and Zn) in the aqueous phase are all below 9 mg/kg under the studied HTC conditions. Graphical Abstract: ga1 Highlights: Biocrude and aqueous phase from HTC of algal biomass were characterized. Biocrude retains up to 50.6% of carbon and 49.8% of energy in algal feedstock. Major inorganic elements in biocrude are K, Fe, Mg, Na, Zn, and Ca. Aqueous phase is rich in organic nitrogen, dihydrogen phosphate, acetate, and K. The concentrations of heavy metals in aqueous phase are below 9 mg/kg.